2010
DOI: 10.1007/s10689-010-9376-z
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma associated with malignancies may herald a hereditary cancer syndrome

Abstract: Two probands with thymoma and other primary malignancies with multiple cancer patients in the family are described. Types of malignancies, pattern of pedigree and age of the patients do not match the known familial cancer syndromes. One proband was a very rare case with five discrete primary malignancies; TP53 sequencing and karyotyping did not reveal any mutations. These cases suggest thymoma associated malignancies may herald a hereditary cancer syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Souadjian et al published one of the first papers on the relation between thymoma and occurrence of other primary cancers, in which the prevalence of other non‐thymic malignant lesions was 21% in thymoma cases in contrast with 8% in parathyroid cancer cases, which was presented as the control group. 7 Also, there are few cases in literature for MPCs, including thymoma; Šitić et al presented an almost similar case of a patient with breast cancer, rectal adenocarcinoma, lung carcinoma, and thymoma 8 ; Tanimura et al reported a series of 97 cases presented with thymoma, in 7 of which another malignant lesion in other organs was also presented (1 case of breast and 1 case of colon) 9 ; Tehrani et al reported 2 cases of MPCs including thymoma 10 ; Athanasiou et al reported a case of MPCs, including thymoma and breast cancer 11 ; and Welsh et al presented 136 cases of thymoma, in which in 38 cases, a second and even a third neoplasm also occurred (12 cases of colorectal carcinoma and 4 cases of breast carcinoma) 12 (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Souadjian et al published one of the first papers on the relation between thymoma and occurrence of other primary cancers, in which the prevalence of other non‐thymic malignant lesions was 21% in thymoma cases in contrast with 8% in parathyroid cancer cases, which was presented as the control group. 7 Also, there are few cases in literature for MPCs, including thymoma; Šitić et al presented an almost similar case of a patient with breast cancer, rectal adenocarcinoma, lung carcinoma, and thymoma 8 ; Tanimura et al reported a series of 97 cases presented with thymoma, in 7 of which another malignant lesion in other organs was also presented (1 case of breast and 1 case of colon) 9 ; Tehrani et al reported 2 cases of MPCs including thymoma 10 ; Athanasiou et al reported a case of MPCs, including thymoma and breast cancer 11 ; and Welsh et al presented 136 cases of thymoma, in which in 38 cases, a second and even a third neoplasm also occurred (12 cases of colorectal carcinoma and 4 cases of breast carcinoma) 12 (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%